2017
DOI: 10.1093/brain/awx338
|View full text |Cite
|
Sign up to set email alerts
|

A widespread visually-sensitive functional network relates to symptoms in essential tremor

Abstract: Essential tremor is a neurological syndrome of heterogeneous pathology and aetiology that is characterized by tremor primarily in the upper extremities. This tremor is commonly hypothesized to be driven by a single or multiple neural oscillator(s) within the cerebello-thalamo-cortical pathway. Several studies have found an association of blood-oxygen level-dependent (BOLD) signal in the cerebello-thalamo-cortical pathway with essential tremor, but there is behavioural evidence that also points to the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 71 publications
8
80
2
Order By: Relevance
“…Using fMRI, studies have reported changes in activation within primary visual cortex, inferior/superior parietal cortex, primary motor cortex, dorsal premotor cortex, and supplementary motor area . In a recent fMRI study consisting of a cohort of ET subjects that overlapped with ET subjects examined in the current work, probabilistic tractography analyses revealed no structural changes within the cerebellum to motor cortex pathway and within the dorsal processing stream linking parietal and motor cortex of ET subjects when compared to controls. The current findings, showing altered connectivity between parietal cortex and motor cortex, complement another EEG study examining coherence between EMG and EEG signals between cerebellum and motor cortex .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using fMRI, studies have reported changes in activation within primary visual cortex, inferior/superior parietal cortex, primary motor cortex, dorsal premotor cortex, and supplementary motor area . In a recent fMRI study consisting of a cohort of ET subjects that overlapped with ET subjects examined in the current work, probabilistic tractography analyses revealed no structural changes within the cerebellum to motor cortex pathway and within the dorsal processing stream linking parietal and motor cortex of ET subjects when compared to controls. The current findings, showing altered connectivity between parietal cortex and motor cortex, complement another EEG study examining coherence between EMG and EEG signals between cerebellum and motor cortex .…”
Section: Discussionmentioning
confidence: 99%
“…We also found reduced bidirectional connectivity between the superior parietal cortex and contralateral motor cortex in ET. Using fMRI, studies have reported changes in activation within primary visual cortex, inferior/superior parietal cortex, primary motor cortex, dorsal premotor cortex, and supplementary motor area . In a recent fMRI study consisting of a cohort of ET subjects that overlapped with ET subjects examined in the current work, probabilistic tractography analyses revealed no structural changes within the cerebellum to motor cortex pathway and within the dorsal processing stream linking parietal and motor cortex of ET subjects when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations